Mothers' Impact on Daughters' Cardiovascular Reactivity in a High‐Threat Context: An Immersive Virtual Environment Study1. (July 2016) - Afifi, Walid A.; Gangi, Katlyn; Blascovich, Jim; Afifi, Tamara D.; Cornick, Jessica E.; Merrill, Anne F.; Ryan, Will; Sterling, Ken
Abstract : Applying Attachment Theory, research on confirmation, the Entropy Model of Uncertainty, and the Biopsychosocial Model of Challenge and Threat, this investigation examined the role of mothers' communication on adolescents' cardiovascular response to threat. An experimental design allowed for the manipulation of maternal response to daughters experiencing a rapidly approaching wildfire in an immersive virtual environment. Results revealed complexities in the relative benefits of maternal vocalic presence during high‐threat situation, with the mother's history of confirming feedback playing an important role in daughters' cardiovascular response. Implications for knowledge are addressed and methodological possibilities of using immersive virtual environments are noted .